Incorporation of probiotic bacteria (Lactobacillus acidophilus and Bifidobacterium ssp.) in Argentinean ovine cheese - Perotti, Maria Cristina (2014)
The market of cheeses from ewe’s milk has been growing steadily in Argentina. The nutritional benefits of these products can be enhanced by adding probiotic cultures. In the present study, the survival of a mix of probiotic microorganisms (Lactobacillus acidophilus La-5 and Bifidobacterium animalis ssp. lactis Bb12) in a semi-hard ovine cheese, manufactured with a technology previously developed in our institute was evaluated. Besides, the effect of its incorporation on the chemical composition and ripening parameters of cheeses, including the fatty acid composition and CLA production, was investigated. Experimental cheeses made with Bb12 and La-5 retained counts of the probiotic strains at the required therapeutic level (107 CFU g−1 ). No significant differences were detected between experimental and control cheeses with respect to the different parameters evaluated: gross composition, nitrogen fractions, lipolysis, fatty acids profiles of cheese fat including CLA, and volatile fraction. Results demonstrated that the ovine cheese matrix seems to be suitable for delivery of probiotic microorganisms.